A Descriptive Report of Early Mobilization for Critically Ill Ventilated Patients With Cancer. Issue 3 (July 2017) - Weeks, Amanda; Campbell, Claudine; Rajendram, Prabalini; Shi, Weiji; Voigt, Louis P.
Abstract : Background: Early mobilization protocols have been successfully implemented to improve function in critically ill patients; however, no study has focused on the oncology population. Objectives: To investigate the feasibility of early mobilization and describe the rehabilitation interventions and discharge outcomes in a cohort of critically ill patients with cancer. Design: Retrospective review. Methods: A retrospective analysis of patients with cancer who participated in occupational and physical therapy while on mechanical ventilation, using an institutional early mobilization protocol from June 2010 to July 2011, was completed. Demographic and clinical variables were abstracted, as well as occupational and physical therapy interventions. Results: A cohort of 42 patients with cancer on mechanical ventilation in the mixed medical/surgical intensive care unit of a comprehensive cancer center received early mobilization during the study period. The majority of participants demonstrated improved cognitive and functional status from the intensive care unit to hospital discharge. There were no reported adverse events during the occupational and physical therapy sessions. Among the 30 hospital survivors, 53% required continued rehabilitation services in their home environment and 40% were transferred to a rehabilitation facility. Limitations: Because of the small sample size, these findings are not generalizable to all critically ill patients with cancer. There was no post–acute care follow-up of cognitive and physical functional performance. Conclusion: Early mobilization appears to be feasible in addressing the cognitive and functional needs of oncology patients in the intensive care unit.